THE EFFECT OF BLENDING OF MTBE IN GASOLINE ON REDUCING LEAD CONTENT - Bustani Mustafa (Testing Center for Oil and Gas LEMIGAS, 1989)
There are two basic incentives in blending MTBE in gasoline for a country like Indonesia , te. To improve the octane quality and to reduce the lead content in gasoline. Changes in physical and chemical properties of gasoline will also occur, accompanying the improvement of the octane number. The blends used in this study were made in four concentrations, viz 3, 6, 10 and 15 volume percent MTBE in unleaded gasoline. The test results were compared to the indonesian specification of premium gasoline.